Pengembangan Modul Pembelajaran Virus Berbasis Web untuk Meningkatkan Kemampuan Berpikir Komputasional dan Pemahaman Konsep Biologi Siswa SMA di Jember - Arinta Mustika Rani (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research aims to develop a web-based biology learning module on virus material with the aim of improving the computational thinking ability and concept understanding of high school students. The research was conducted using the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Data was obtained through expert validation, readability questionnaires, and student pre-test and post-test. The results of the study show that the developed one has a high level of validity with an average score of 84%. The practicality test obtained a student readability result of 83.3%, which was categorized as very practical. The effectiveness test showed an increase in learning outcomes with an average N-gain score of 0.65 which belongs to the medium category. This web-based module is able to increase students' motivation to learn, computational thinking and understanding of biology concepts. Based on this study, the web-based virus learning module is valid, practical, and effective enough to be used in biology learning in high school. This module is expected to be an alternative teaching material that supports interactive and innovative learning
Entry oleh Arif 2026 Maret 16
Keywords: Learning Modules; Computational Thinking; Concept Understan